Menjadi Pembawa Kabar Sukacita: Belajar dari Respons Para Gembala dalam Lukas 2:15 - Jonidius Illu; Eliyunus Gulo; Nehemia Nome; Merry Wati Rosdiana (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2025)
This article highlights the significance of believers as bearers of the good news, drawing upon the response of the shepherds in Luke 2:15. In contemporary Christianity, many believers appear passive or hesitant in proclaiming the gospel, often due to misconceptions such as the notion that evangelism amounts to proselytism, that it ought to be replaced by interreligious dialogue or apologetics, or that doing good alone is sufficient for salvation. This study seeks to recover the missional example of the shepherds, who actively shared the message with those who had not yet heard it. Employing a qualitative descriptive approach through biblical textual analysis, the study examines the theological significance of the shepherds’ response. The findings indicate that the shepherds not only received and witnessed the good news but also became its earliest messengers. Their response offers a model for believers today: to embrace their calling to proclaim Christ, that others too might come to faith.